Ab initio formation energies and time-dependent density functional theory excitation energies for nickel–nitrogen defect sites in diamond nanoparticles. (19th March 2018) - Gothard, Nicholas W.; Dudis, Douglas S.; Bissell, Luke J.
Abstract: Abstract : Diamond stands out in its ability to host hundreds of color centers, the most studied of which may be the nitrogen-vacancy and NE8 centers. The NE8 center, in particular, can generate single photons at an energy of 1.56 eV, but synthesis efforts are low yield and lack precise control of the defect structure and resulting optical properties. Complementing a bottom-up synthesis effort, we develop a rapid-screening computational approach for screening potential color centers in nanodiamond, focusing here on the nickel–nitrogen complexes. Formation and optical absorption energies are characterized with respect to defect stoichiometry and structure.